2019
DOI: 10.1111/jce.14042
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of acquired pulmonary vein stenosis after radiofrequency ablation for atrial fibrillation—Is routine follow‐up imaging indicated or not?

Abstract: Introduction Thermal injury during radiofrequency ablation (RFA) of atrial fibrillation (AF) can lead to pulmonary vein stenosis (PVS). The aim of the present study was to analyze the natural course of RFA‐induced PVS with regard to the grade of stenosis, clinical symptoms, and mortality during long‐term follow‐up. Methods and Results All patients with follow‐up imaging for radiofrequency‐induced untreated PVS were retrospectively assessed. From 2004 to 2017, the total rate of PVS following AF ablation in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These risks are rare but include PV stenosis and stiff LA syndrome. 8,9,17 Many of the randomized clinical trials, which have demonstrated superiority of catheter ablation over antiarrhythmic drug therapy, included repeat ablation procedures as part of their prospective study designs. 1,10,11,18 Randomized data also suggest that repeat ablation is superior to antiarrhythmic drug therapy for the treatment of recurrent AF after first ablation.…”
Section: Rhythm Controlmentioning
confidence: 99%
“…These risks are rare but include PV stenosis and stiff LA syndrome. 8,9,17 Many of the randomized clinical trials, which have demonstrated superiority of catheter ablation over antiarrhythmic drug therapy, included repeat ablation procedures as part of their prospective study designs. 1,10,11,18 Randomized data also suggest that repeat ablation is superior to antiarrhythmic drug therapy for the treatment of recurrent AF after first ablation.…”
Section: Rhythm Controlmentioning
confidence: 99%
“…Oesophageal injury can be visualized with both CCT [26] and CMR with LGE [27]. Similarly, patients with suspected pulmonary vein stenosis can be imaged via CCT or CMR [28].…”
Section: Anatomic Delineationmentioning
confidence: 99%
“…The latter may require PV angioplasty and large diameter bare‐metal stent placement with a substantial number of patients developing in‐stent restenosis 2 . By contrast, moderate PV stenosis is unlikely to progress over time putting into question the need for routine follow‐up imaging in asymptomatic patients 3 …”
mentioning
confidence: 99%
“…2 By contrast, moderate PV stenosis is unlikely to progress over time putting into question the need for routine follow-up imaging in asymptomatic patients. 3 Balloon technologies are designed to target the antral portion of the PV ostium. Selecting a sufficiently large balloon-to-PV ratio should mitigate the risk of inadvertent energy delivery inside the PV ostium.…”
mentioning
confidence: 99%